HUBUNGAN PENDIDIKAN DAN MOTIVASI DENGAN PEMBERIAN ASI EKSLUSIF DI PMB NY E KABUPATEN BOGOR - Widyasari, Reny; Karlina, Haura; Rimanda, Ayu (Jurnal Ilmiah Kesehatan BPI, 2025)
Background: Breast milk or breast milk is the most recommended food for babies, at least for the first 6 months. Exclusive breastfeeding coverage in the world is around 44% (WHO, 2022). Based on the results of the 2022 Indonesian Nutrition Survey, it was recorded at 67.96%. According to the results of 2018 (RISKERDAS) data, it shows that the proportion of breastfeeding patterns for babies aged 0-6 months in Indonesia is 37.3%, according to the Bogor District Health Service (2021) it is 48.58%. The aim of this research is to determine the relationship between education and motivation with exclusive breastfeeding in PMB Ny E, West Cilebut village in 2024. Method Using quantitative research, the population of this research is mothers who have babies aged 7-12 months. Based on data from Mrs E's PMB in 2024, there were 56 people using non-probability sampling techniques. The results of the chi square test research were that there was a significant relationship between education level and exclusive breastfeeding, with a p value of 0.004 < α (0.05). The results of statistical tests between motivation and exclusive breastfeeding showed that comparative motivation was low motivation, low motivation with a moderate p value of 0.010 > α (0.05), low motivation with a high p value of 0.002 < α (0.05), it can be concluded that there is a relationship There is a significant relationship between motivation and exclusive breastfeeding in the Ny E PMB area in 2024. Suggestion: Can provide health promotion related to the importance of breast milk to the community so that the community is able to implement Exclusive Breastfeeding.